A STUDY ON CLOUD COMPUTING ADOPTION IN E-BUSINESS - H.S. Lim; Wahidah Husain (Jurnal Sistem Informasi, 2013)
Cloud computing is an undeniable shift paradigm due to the rapid advancement in processors, distributed grid computing, disk storage and performance, Internet networking and virtualization techniques. Adoption of cloud computing in business creates some considerable business values. So basically this paper will concentrate on the study of the cloud adoption in business. Besides, this paper also aims to investigate the business benefit gained by adopting cloud computing in the business as well as the key challenges of cloud adoption in business.